Peran Strategis Bahasa Indonesia: Komunikasi Efektif Sebagai Kunci Keberhasilan dalam Aktivitas Manajemen Perkantoran - Ramadhan, Sashi Azka; Husna, Sayyidati Is’faalana; Ningrum, Rika Cantika Kemala; Rizkiyani, Shalsabila; LS, Silvia Nur Fitroh; Rizkyanfi, Mochamad Whilky (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the strategic role of the Indonesian language in effective communication as a key to success in office management activities. The method used is a descriptive qualitative approach. The researcher chose this approach to describe in detail the role of the Indonesian language in formal communication and its relation to achieving organizational goals. Data were collected through interviews with several private employees from various divisions and job positions. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The interview results revealed several obstacles in achieving effective communication in the workplace, both spoken and written. The use of proper and correct Indonesian was seen as the main solution to these challenges. The Indonesian language is considered essential for maintaining communication that is clear, efficient, and well-structured across departments and between superiors and subordinates. Effective communication serves as the foundation for aligning understanding, accelerating workflows, and preventing misunderstandings that may hinder the achievement of company objectives. Thus, it can be concluded that the strategic use of the Indonesian language in the workplace plays a vital role in supporting effective and efficient communication. This strategic role makes it a key element in the successful execution of professional, results-oriented office management activities.